Chemical composition and antimicrobial activity of Gannan navel orange (Citrus sinensis Osbeck cv. Newhall) peel essential oils. Issue 6 (14th June 2018) - Guo, Qingyun; Liu, Ke; Deng, Weihui; Zhong, Balian; Yang, Wenxia; Chun, Jiong
Abstract: The present investigation reported the chemical composition of cold pressed Gannan navel orange peel essential oil (EO) and its molecular distillation fraction (light phase EO), and examined their antimicrobial activity against spoiling and pathogenic microorganisms. Gas chromatography‐mass spectrometry analysis identified 27 and 20 different chemical constituents in cold pressed EO and light phase EO, respectively. Limonene was the major constituent, accounting for 85.32% of cold pressed EO and 60.44% of light phase EO. Both EOs and some of their constituents showed good antimicrobial activity. Compared to cold pressed EO, light phase EO exhibited the better antimicrobial activity under weak acidic and neutral conditions. The light phase EO presented a higher antimicrobial activity after thermo‐treatment at 60–100°C for 20 min than cold pressed EO. These results demonstrated that light phase EO had a potential to be used as a novel antimicrobial agent for food preservation and food processing. Abstract : Chemical composition of cold pressed and light phase orange EOs was identified by GC‐MS. Both EOs and some of their constituents showed good antimicrobial activity. Light phase EO exhibited better activity under weak acidic and neutral conditions than cold pressed EO.